A large memory window and low power consumption self‐rectifying memristor for electronic synapse. Issue 2 (16th January 2023) - Li, Qingjiang; Yu, Shihao; Yang, Peng; Wang, Qin; Liu, Sen
Abstract: Self‐rectifying memristor has no need for selector devices, but possesses the one‐way transmission behaviour and multi‐level non‐volatile memory characteristics, which makes it a promising candidate for electronic synapse. In this letter, the authors propose a novel self‐rectifying memristor based on a Pt/Hf0.5 Zr0.5 O2 /TiN structure. The devices show large memory window (10 4 ) and high rectifying ratio (10 4 ), which can block the sneak current in a passive crossbar array without any additional hardware overhead. Moreover, the devices demonstrate excellent multi‐level states modulation capability, low power consumption, high endurance and long retention. The final benchmark demonstrates that the proposed Pt/Hf0.5 Zr0.5 O2 /TiN self‐rectifying memristor is a promising candidate for electronic synapse application. Abstract : Different from other memristors, the self‐rectifying memristors possess the similar one‐way transmission characteristic as biological synapses, making these devices better to mimic the synaptic plasticity. In this letter, the authors propose a novel self‐rectifying memristor based on the Pt/Hf0.5 Zr0.5 O2 /TiN structure. The device shows competitive advantages, large memory window (10 4 ) and high rectifying ratio (10 4 ).